Cosmic Filament Spin. II. Filament Spin and Its Impact on Galaxy Spin–Filament Alignment in a Cosmological Simulation - Wang, Peng; Tang, Xiao-xiao; Wang, Hao-da; Libeskind, Noam I.; Tempel, Elmo; Wang, Wei; Zhang, Youcai; Sheng, Ming-Jie; Yu, Hao-Ran; Xu, Haojie (The Astrophysical journal, 2025)
Observational studies have reported that cosmic filaments on the megaparsec scale exhibit rotational motion. Subsequent simulation studies have shown qualitative agreement with these findings, but quantitative discrepancies remain due to differences in data and methods, which require verification. To address this issue, we adopt the same methodology as used in the observations to identify filament spin from the galaxy distribution constructed from a hydrodynamic simulation. Using the same approach to measure filament spin, we find that the simulation results closely match the observational findings, with only minor discrepancies arising from slight differences in the fraction of filaments classified as dynamically cold or hot based on their dynamic temperature. Additionally, an analysis of how filament spin affects the galaxy spin–filament correlation shows that dynamically cold filaments with strong spin signals have a greater impact on the galaxy spin–filament correlation than those with weaker spin signals and dynamically hot filaments. These results not only provide further evidence that cosmic filaments exhibit spin but also highlight the importance of this rotation in the acquisition of angular momentum by individual galaxies. Future studies exploring the influence of filament spin on galaxy spin may shed light on the physical origins of filaments and the angular momentum of galaxies.